Pathogenic mechanisms and therapeutic potential of the microbiome in premature ovarian insufficiency - Ma, Shuai; Zheng, Lianwen; Zhuang, Xiaohua; Wang, Min; Zou, Yinggang (Frontiers in Immunology, 2025)
The postponement of childbearing age has become a global issue. Factors such as increased work pressures on women and environmental changes have led to a rising incidence and younger onset of premature ovarian insufficiency (POI). POI not only impacts patients’ reproductive function but also heightens the risk of depression, anxiety, cognitive decline, premature mortality, osteoporosis, and cardiovascular disease. Exploring effective prevention and treatment strategies for POI can slow ovarian ageing and safeguard female reproductive health. Microbiome research confirms that most human tissues and organs form dynamic, interactive systems with symbiotic microbes that play a crucial role in female reproductive function. Previous studies on the microbiome and female reproductive health have rarely focused on POI. The proposed ‘Microbiota-Ovary Axis’ aims to establish an integrated regulatory framework. This theoretical model systematically elucidates how microbial signals influence ovarian function through four core pathways: the hypothalamic-pituitary-ovarian (HPO) axis, metabolism and endocrine regulation, immunoregulation, and oxidative stress. Evaluating the efficacy of dietary modifications, probiotics, and microbiota transplantation in animal models and preliminary clinical studies will establish a robust theoretical foundation for developing microbiota-targeted innovative diagnostic and therapeutic strategies for POI, thereby enhancing reproductive health throughout the female lifespan.